The Effectiveness of Using Wattpad on Development Students’ Writing Ability - Ance Jusmaya (IdeBahasa, 2019)
The purpose of this study is to look for a significant influence on the application of using Wattpad as learning activities on students' ability to write descriptive texts. The main consideration is because an educator in this case should used interesting instructional media, particularly to teach writing so that the potential of students can be developed optimally. Meanwhile the development of writing of English Department Students of Putera Batam University is still relatively low in quality. Wattpad is an applications which provides the students an opportunity to write, promote and help their writing reach acroos the world. The design of the research was quasi-experimental research that want to find out the effect of using Wattpad towards students writing ability. To know students’ writing ability, this research uses writing test as Instrument. There are three pre tests and post tests. The pre-test were used to see students writing ability before having treatment and posttest are used to see the differences on students writing ability after giving treatments. The subjects were the students of English Department of Putera Batam University who took writing class. The data found that using Wattpad has a significant effect on student’s writing ability. This conclusion can be seen based on the analysis that has been done where the obtained Z score was smaller than critical value, the null hypothesis (Ho) was rejected and alternative hypothesis (Hi) was accepted. So, based on the results , it was concluded that there was statistically diffrence between the pre-test and post-test score at the 0.05 levels. It means that teaching writing by using wattpad gives significant effect on students’ writing ability